Meningkatkan Kemampuan UMKM “Es Teh Nusantara” dalam Mengelola Keuangan dengan Menggunakan Konsep Ekonomi Manajerial - Etty Zuliawati Zed; Adinda Zalfaa; Amara Pristania; Frasasti Mawar; Suherman Suherman (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This community service activity successfully initiated simple financial recording practices in MSME “Es Teh Nusantara”, addressing the initial condition where the MSME had no formal financial records. This initiation not only increased the awareness of MSME owners and staff about the importance of financial management but also equipped them with practical skills in recording daily transactions, which is a crucial foundation for more effective financial management. Furthermore, this activity paved the way for a broader understanding of managerial economics concepts, such as the importance of understanding costs in pricing decisions. A gradual approach, starting with simple recording and supported by mentoring tailored to the specific needs of micro-enterprises, proved effective in initiating positive changes in business financial management and creating the potential for more sustainable business development.